Analysis of Influence Law of Burial Depth on Surrounding Rock Deformation of Roadway - Hai Wu; Xiaokang Wang; Weijian Yu; Weijun Wang; Zizheng Zhang; Gang Peng (Advances in Civil Engineering)
In order to study the influence of burial depth on the roadway deformation, the deformation data of more than 100 roadways were collected and classified. The results have shown that, in the first 5 days of new digging roadways, the surrounding rock deformation is basically not affected by the buried depth. The influence period of roadway deformation with different depths is the same, namely, the severe period (1∼15 days), the mitigation period (15∼35 days), and the stable period (35∼50 days). With the increase in depth, the surrounding rock deformation increment of new digging roadways with a depth of 300∼600 m is much larger than that of 600∼900 m. Within 100 m of the working face from the monitoring point, the deformation of mining roadways can be divided into two stages: severe impact (10∼60 m) and stable impact (60∼100 m). With the increase in depth, the deformation increment of the surrounding rock in the mining roadways with a depth of 600∼900 m is much larger than that of 300∼600 m. The surrounding rock deformation increases with the increase in the width and height of roadways and gradually increases with the decrease in the strength of rock mass.